Метаболізм прилеглої до пухлини жирової тканини та маса тіла хворих на колоректальний рак III–IV стадії - Бурлака, А.П.; Вовк, А.В.; Бурлака, А.А.; Звірич, В.В.; Лукін, С.М.; Вірко, С.В. (Онкологія, 2018)
Жирова тканина, в оточенні якої розвиваються солідні пухлини (особливо за наявності ожиріння), може бути одним із факторів мікрооточення з пропухлинними властивостями. Мета: дослідити рівні оксиду азоту (NO) та супероксидних радикалів (СР) у прилеглій до пухлини жировій тканині (ППЖТ), а також концентрацію вільних жирних кислот (ВЖК) в крові хворих на колоректальний рак (КРР) ІІІ–IV стадії залежно від маси тіла пацієнтів, ступеня диференціювання пухлини, об’єму метастазів (М) у печінці. Об’єкт і методи: зразки ППЖТ хворих на КРР з ожирінням (індекс маси тіла (ІМТ) > 25; n = 84) та без його ознак (ІМТ < 25; n = 47). За контроль (нормальна жирова тканина — НЖТ) вважали матеріал від 18 пацієнтів з доброякісними новоутвореннями. Швидкість генерування СР мітохондріями та рівень NО в зразках жирової тканини визначали методом електронного парамагнітного резонансу (ЕПР) при кімнатній температурі та низькотемпературному режимі з використанням відповідних спінових уловлювачів. Вміст ВЖК у крові визначали спектрофотометричним методом при λ = 546 нм. Результати: активність FeS-білків електронно-транспортного ланцюга (ЕТЛ) мітохондрій у ППЖТ хворих на КРР (ІМТ > 25) була достовірно вищою порівняно з такою в НЖТ; рівень убісеміхінону в ППЖТ в 11 разів перевищував показник НЖТ. У ППЖТ виявлено також зростання рівня активності молібденвмісних ферментів, що свідчить про накопичення в ній токсичних продуктів розпаду пуринів та альдегідів. Рівень CР у ППЖТ хворих на КРР з ІМТ > 25 був у 5,6 та 1,3 раза вищим, ніж в НЖТ та у хворих без ожиріння відповідно. Рівень NO в ППЖТ хворих з ІМТ > 25 був достовірно нижчим, ніж в НЖТ, у ППЖТ хворих без ожиріння не відрізнявся від останнього (р > 0,05). Рівень ВЖК у крові хворих на КРР незалежно від наявності ознак ожиріння перевищував (р < 0,05) даний показник у донорів (ІМТ > 25). В жировій тканині, прилеглій до G1–3-пухлин, рівні NO достовірно не відрізнялися, проте були нижчими порівняно з НЖТ (р < 0,05). У хворих з морбідним ожирінням (ІМТ > 40) середній об’єм М був достовірно більшим (р < 0,05), ніж у хворих з ІМТ < 40. Висновки: вираженість та напрямок змін низки характеристик жирової тканини хворих на КРР III–IV стадії (спектри ЕПР ППЖТ, рівні NO та СР, концентрація ВЖК у крові) мають незаперечний зв’язок із масою тіла пацієнтів: за наявності різних ступенів ожиріння метаболічні порушення збільшуються. У пацієнтів з морбідним ожирінням відмічали найбільший об’єм М у печінці. З урахуванням одержаних результатів селективне NO-залежне регулювання транспорту електронів у ЕТЛ мітохондрій, зокрема в ППЖТ, для впливу на витрату енергії може бути ефективною складовою в стратегії лікування пацієнтів із КРР. Obesity is a pathological accumulation of hypertrophied adipocytes, which may be an unfavorable factor in the formation of tumor cell chemo-resistance and the progression of malignant neoplasms (local relapses, metastases). A critical molecule that influences the growth and metastasis of tumors is nitric oxide (NO), which can damage DNA, suppress the DNA repair enzymes, regulate apoptosis and metastasize. Proliferation of tumor cells, angiogenesis, metastases are closely related to the functioning of NO and superoxide radicals (SR). Objective: to investigate the levels of NO and SR in adjacent adipose tissue (AAT), as well as the concentration of free (un-esterified) fatty acids (FFA) in the blood of patients with colorectal cancer (CC) stage III–IV, depending on the weight of the patient’s body, degree tumor differentiation, volume of metastases (M) in the liver. Object and methods : samples of AATs of patients with CC of the III–IV stage with obesity (body mass index (BMI) > 25; n = 84) and without its signs (BMI < 25; n = 47). For control (normal adipose tissue — NAT) considered the material from 18 patients with benign neoplasms. The rate of generation of SR by mitochondria and the NO level in the samples of the adipose tissue were determined by the method of electron paramagnetic resonance (EPR) at room temperature and at low temperature using appropriate spin traps. The content of FFA in blood was determined by spectrophotometric method at λ = 546 nm. Results: the activity of FeS-proteins of the electron transport chain (ETC) of mitochondria in the AATs of patients with CC (BMI > 25) was significantly higher compared to that in NAT; the level of ubisemichinon in AAT was 11 times higher than that of NAT. An increase in the level of activity of molybdenum-containing enzymes (xanthine and aldehyde oxidase) was also observed in AATs of patients with CC, indicating accumulation of toxic products of decomposition of purines and aldehydes in it. The level of SR in AAT patients with CC with BMI > 25 was 5.6 and 1.3 times higher than in the NAT and in patients without obesity (BMI 18.5–25), respectively. The level of NO in AAT patients with BMI > 25 was significantly lower in comparison with NAT, in AAT of patients without obesity did not differ from such in NAT (p > 0.05). The level of FFA in the blood of patients with CC, regardless of the presence of signs of obesity (with BMI 18.5–25 and > 25), exceeded this indicator in donors (BMI > 25) by 3.4 and 6.0 times, respectively (p < 0.05). In the adipose tissue, adjacent to the G1–2- and G3- tumors, NO levels were significantly different, however, they were lower in 2.0 and 2.5 times than in NAT (p < 0.05). In patients with morbid obesity (BMI > 40) the average volume of M was 19.75 ± 5.9 cm 3. Volume M was significantly lower in patients with BMI < 40: at BMI 18.5–24.9 was 4.33 ± 2.6 cm 3 , with BMT 25– 40 — 8.40 ± 3.7 cm 3. Conclusions : the severity and direction of changes in a number of characteristics of the adipose tissue of patients with CC of III–IV stage (spectra of AAT EPR, NO and SR levels in AAT compared with NAT, the concentration of FFA in blood) has an indisputable link with the weight of patients: in the presence of different degrees of obesity metabolic disorders increase. In patients with morbid obesity, the largest volu me of M in the liver was observed. Based on the results obtained, selective NO-dependent regulation of ETC in mitochondria, in particular, in AAT, to influence energy expenditure can be an effective component in the strategy of treatment of patients with CС.